Oil and gas generation potential of the Middle Jurassic coals of the Ulug-Khem Basin (South Siberia, Russia) - Solangy A. Ondar; Dmitry A. Bushnev; Natalia A. Smirnova (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The Middle Jurassic carbonaceous deposits of the Ulug-Khem basin (Republic of Tuva, Russia) are an available for studying stratigraphic analogue of the source rocks of the oil and gas basins of China (Xishanyao formation J2x) and Western Siberia (Tyumen formation J2tm). The study of their generation properties will allow us to predict the distribution zones of coal-bearing source rocks in adjacent poorly studied areas. Aim and methods. Assessment of the hydrocarbon potential of the Ulug-Khem basin coals based on the results of Rock-Eval pyrolysis. Results. According to pyrolysis data the Middle Jurassic coals of the Ulug-Khem basin have significant hydrocarbon potential. Kerogen is represented by a mixture of types II and III, vitrinite and liptinite in different proportions. The liquid and gaseous hydrocarbons generation potential of coals from the Mezhegey and Elegest coal fields has been mostly realized. The amount of hydrocarbons that could have been produced by the coals reaches very high values – 100–170 mg HC/g of rock. Comparison of the Ulug-Khem basin coals and the Middle Jurassic source rocks of Western Siberia and a number of basins in China shows the similarity of their organic matter. The hydrocarbon generation potential of the organic matter of the Middle Jurassic coals and their analogues can be realized in the sedimentary basins of Mongolia.